Synthesis, characterization crystal structures and DNA binding studies of zinc complexes with oxygen and nitrogen donor ligands. (1st February 2020) - Mehr-un-Nisa,; Sirajuddin, Muhammad; Ali, Saqib; Tahir, Muhammad Nawaz; Iqbal, Muhammad
Graphical abstract: The complexes interact with SS-DNA via intercalation mode of interaction resulting in hypochromic effect and significant red shift as well as increasing the length of SS-DNA that result in the increase in viscosity of the DNA-compound adduct formed. Highlights: Synthesis of mononuclear and bi-nuclear zinc(II) complexes. Characterization through FT-IR, UV–Visible, 1 H- and 13 C NMR spectroscopy and single crystal XRD techniques. Structural description. DNA-binding studies. Abstract: Three zinc metal complexes viz, [Zn(L 1 )2 phen] (1 ), [Zn2 (L 2 )4 (bipy)2 ] (2 ) and [Zn(L 2 )2 bipy·H2 O] (3 ) where HL 1  = 4-( o -toluidino)-4-oxobutanoic acid and HL 2  = 4-(4-nitrophenyl amino)-4-oxobut-2-enoic acid, bipy = 2, 2-bipyridine and phen = 1, 10-phenenthroline. To elucidate their structure and geometry, the synthesized complexes were characterized by different analytical techniques such as FT-IR, 1 H NMR, 13 C NMR and single crystal X-ray diffraction analysis. Single crystal X-ray analysis confirmed slightly distorted square pyramidal geometry for complex 2 and distorted octahedral geometry for complexes 1 and 3 . To explore the applications of synthesized complexes, their DNA binding studies were performed by viscometry and UV–Visible spectroscopy. By using these techniques, binding constants with DNA and Gibb's free energy change was calculated of synthesized complexes. All the complexes showed spontaneous binding with DNA with Kb values 7.05 × 10 4, 1.06 × 10 4, 1.6 × 10 4  M −1 and the Gibb's free energy ΔG = −27.6, −22.9 and −23.8 kJmol −1, respectively for complexes 1 –3 .